Two - phase approach for solving linear programming problem with generalized intuitionistic trapezoidal fuzzy numbers - Dinagar, D. Stephen; Thiripurasundari, K. (2012 International Conference on Advances in Engineering, Science and Management, 2012)
In this article, a new generalized two phase algorithm to solve the linear programming problems with the aid of generalized intuitionistic trapezoidal fuzzy numbers(GITrFNs) is proposed. New arithmetic operations on GITrFNs are defined to develop the proposed notion. A relevant numerical example to illustrate the discussed notion is also included.